Hepatic YAP1-TFE3 Rearranged Epithelioid Hemangioendothelioma. (23rd June 2019) - Lotfalla, Mira M.; Folpe, Andrew L.; Fritchie, Karen J.; Greipp, Patricia T.; Galliano, Gretchen G.; Halling, Kevin C.; Mounajjed, Taofic; Torres-Mora, Jorge; Graham, Rondell P.
Abstract : Epithelioid hemangioendothelioma (EHE) is an uncommon low-grade malignant vascular tumor that may arise in soft tissue/bone or visceral sites such as the liver and lung. As this tumor exhibits epithelioid morphology, it frequently causes diagnostic confusion with other epithelioid vascular neoplasms as well as carcinoma. While 90% of classic EHE are driven by a WWTR1-CAMTA1 fusion gene, a histologically distinctive subset of EHE has been recently shown to harbor a different fusion gene, YAP1-TFE3 . This variant is likely underrecognized given its rarity and only recent description. Notably, EHE frequently involves the liver but only one case of hepatic YAP1-TFE3 rearranged EHE has been reported to date. We present the second case of YAP1-TFE3 rearranged EHE affecting a 65-year-old woman and presenting as multiple liver masses, with characterization of the fusion gene at the transcriptomic and genomic levels. There are several educational points noted from this case. YAP1-TFE3 rearranged EHE shows distinctly vasoformative foci, unlike classic EHE and mimicking angiosarcoma or epithelioid hemangioma. The tumors cells show a histiocytoid appearance with voluminous cytoplasm, similar to other TFE3- rearranged tumors. Finally, in the liver, this tumor may in part mimic focal nodular hyperplasia of the liver which is an underrecognized diagnostic pitfall. This report highlights the key diagnostic and genetic features of this newly recognized variant of hepatic EHE to aid pathologists in appropriately classifying these tumors.